Faktor demografi dan obstetrik dalam mempengaruhi kualitas hidup postpartum - Risky Puji Wulandari; Mufdlilah Mufdlilah (Jurnal Kebidanan, 2020)
The postpartum period is one of the critical transition periods in women's lives, both physically and psychologically. The low quality of life for women, especially postpartum mothers, is caused by the postpartum period's needs in the form of physical, psychological, and social needs. Women who have an essential role, mature basis and quality of life are important to measure postpartum care accuracy. The purpose of this study was to determine the factors that affect the quality of postnatal life in the work area of Mertoyudan I Health Center, Magelang Regency. This type of research is quantitative research with a cross-sectional research design. The sampling technique used accidental sampling. The number of samples in this study was 60 postpartum mothers. The research instrument was a questionnaire on demographic factors (age, education, residence status, occupation, stage), obstetric questionnaires (parity, type of baby present, history of pregnancy, history of abortion, desired pregnancy, and breastfeeding factors), and the Postpartum Quality of Life questionnaire. (PQOL). The study results with the results of the Chi-Square statistical test prove that there is an influence of demographic factors including age, education, and stage variables on the quality of life postpartum with p-value 0.003 <0.05, p-value 0.001 <0.05, and p-value 0.002 <0.05. Obstetric factors including parity, history of complications, history of abortion, desired pregnancy, and breastfeeding factors influence the quality of life postpartum with p-value <0.050, p-value <003, p-value <0.040, p-value <0.000, p-value value <0.017, and p-value <0.002.